Burden of Proof in the Collective Environment Protection: A perspective to enforce environmental protection (Research, Society and Development, 2021)
The purpose of this study is to analyze the procedural rule from a perspective aligned with effective protection of fundamental rights and guarantees. The dynamics of the burden of proof are discussed based in the principles of precaution and environmental prevention. An argument develops that the dynamic distribution of the burden of proof in the class actions envolving environmental suits would be compatible with the effectiveness of jurisdictional protection, with a view to promoting the right to an ecologically balanced environment. It is a theoretical-bibliographical-natured research guided by a descriptive-analytical method which had instructed the analysis of constitutional and infraconstitutional laws, as well as the doctrine informing the concepts of dogmatic order.